Georgia : 2011 Article IV Consultation-Staff Report; Staff Supplements; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Georgia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The government of Georgia moved forcefully to counter the economic impact of the August 2008 conflict with Russia and global financial crisis. Monetary and prudential policy easing was, however, unable to prevent a sharp credit squeeze. The economy is recovering at a solid pace, with real GDP growth expected to exceed 6 percent in 2010. To reduce exposure to changes in external market conditions, the authorities could rely more on domestic financing. Macroeconomic policies were generally aligned with previous IMF recommendations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet